Banana Peel: A Green and Economical Sorbent for the Removal of Heavy Metals from Industrial Wastewater - Gupta, C. Ramalingam*, Sweta Rai and Sonica (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Industrial effluents cause main threat to the rural areas and the living habitat of the ecosystem. Biological waste has the potential to reuse it in productive output. This study describes the use of banana peel, a commonly produced fruit waste, for the removal of heavy metals like Cr, Cd, etc from industrial wastewater. The high concentration of metal ions in effluents causes concern because of their carcinogenic properties, non-biodegradability and bio-accumulation. Cadmium causes metabolic disorders such as itai-itai disease, testicular atrophy, hypertension, emphysema and renal damage. While Cr (VI) causes acute tubular & glomerular damage, chronic ulceration of other skin surfaces, asthma and cancer of the respiratory tract. Effluents from industries like tannery industry, chrome plating, metal finishing, oil refinery, electroplating, nickel-cadmium batteries, fertilizers and dyes contains Cr and Cd. Rice straw,Â  raw seaweed, tea factory waste, maize cob, bagasse, and sawdust are generally used as biosorbents. But these have other uses as well when compared to banana peel. Banana peel is suitable as biosorbent due to its easy availability and high sorption capacity of heavy metals due to the presence of functional groups like -COOH, -OH, esters and amines.